The Effect of Poverty Level on Human Development Index (HDI) in North Sumatera Province in 2018 - Nasution, Armin Rahmansyah; Handayani, Annisa; Rinaldi, Rinaldi; Angelia, Tina; Siahaan, Tegar Efraim Gilbert; Hutabarat, Febry Br (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
Development is a planned process of social change to improve the quality of life. In improving human development, welfare equalization is necessary because it is an important aspect of human development. Unfortunately, poverty is a major obstacle in achieving welfare equality. Therefore, this study was made with the aim of examining the relationship between the poverty rate and the Human Development Index (HDI) in North Sumatra Province. This research is a quantitative research, data collection using secondary data sourced from books, journals relevant to the current research and reports at the Central Statistics Agency (BPS) of North Sumatra Province. The data studied includes the poverty rate and human development index (HDI) in North Sumatra for the 2018 period. Based on data from BPS North Sumatra Province in 2018, the results found that the poverty rate has a negative and significant effect on the Human Development Index.